HIPNOSI (Lactation Hypnosis) for Improving Breast Milk Production - Widayanti, Wiwin; Sari, Vianty Mutya; Aliah, Nur; Tonasih, Tonasih (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Problems can arise during the breastfeeding process, including the release of breast milk. Problems with breastfeeding can have an impact on the mother's psychology, which greatly affects the work of the hormone oxytocin. HIPNOSI (Lactation Hypnosis) is a solution to overcome the problem of breastfeeding by programming positive suggestions to stimulate the release of the hormone oxytocin, and lactation problems can be resolved. This study aim was to determine the effect of HIPNOSI (Lactation Hypnosis) for improving the breast milk production in health care centers in Cirebon area.Methods: This type of research is a quasi-experimental, post-test only design with a control group, respondents are breastfeeding mothers. The research sample used the determination of sample size in a simple experimental study of 30 respondents who were divided into treatment and control groups. Sampling used consecutive sampling, milk production was measured once, data was analyzed using the Mann-Whitney test.Results: Univariate analysis showed that most of the milk output in the intervention group was 15 ml, 16.5 ml, 18 ml, 39 ml, 81 ml, respectively 100%. While the milk output in the control group was mostly 2.5 ml, 5 ml, 6.5 ml, respectively 100%. Statistical test results obtained p value = 0.001 means that there is an effect of the HIPNOSI (Lactation Hypnosis) method on breastfeeding.Conclusion: HIPNOSI (Lactation Hypnosis) method has an effect in helping to expedite the release of breast milk and can produce more milk production